Pathogenesis of Herpes Stromal Keratitis: Immune Inflammatory Response Mediated by Inflammatory Regulators - Wang, Li; Wang, Runbiao; Xu, Chuyang; Zhou, Hongyan (Frontiers in Immunology, 2020)
Herpes stromal keratitis (HSK) is one of the primary diseases that cause vision loss or even blindness after herpes simplex virus (HSV)-1 infection. HSK-associated vision impairment is predominantly due to corneal scarring and neovascularization caused by inflammation. In the infected cornea, HSV can activate innate and adaptive immune responses of host cells, which triggers a cascade of reactions that leads to the release of inflammatory cytokines, chemokines, microRNA, and other regulatory factors that have stimulating or inhibitory effects on tissue. Physiologically, host cells show homeostasis. In this review, we summarize the factors involved in HSK pathogenesis from the perspective of immunity, molecules, and pathological angiogenesis. We also describe in detail the pathogenesis of chronic inflammatory lesions of the corneal stroma in response to HSV-1 infection.